The Relationship of the Implementation of Discharge Planning with the Level of Patient Satisfaction in the Inpatient Health Center - Nanda Puspita Sari; Dian Utama Pratiwi Putri; Rustika Rustika (Indonesian Journal of Global Health Research, 2025)
Discharge planning that is not yet optimal has an impact on patients. This impact is an increase in the number of re-admissions and ultimately patients will bear the costs of inpatient care at the health center. The aim of this research is to find out the relationship between the implementation of discharge planning and the level of patient satisfaction at the Banjar Agung Inpatient Health Center, South Lampung Regency in 2024. This type of research is quantitative using a crosssectional approach. The population and sample in this study were all inpatients from January-April 2024, totaling 47 respondents. The sampling technique used is quota sampling, The sample was determined from a population with certain characteristics to the desired number (quota) of 47 patients. Based on the results of statistical tests, the P-value < 0.05 was obtained, namely the satisfaction variable 0.014, the tangible variable 0.007, the reliability variable 0.041, the responsiveness variable 0.000, the assurance variable 0.034 and the empathy variable 0.017, which means that there is a relationship between the implementation of discharge planning and the level of patient satisfaction based on dimensions. Tangible at the Banjar Agung Inpatient Health Center, South Lampung Regency in 2024.